THE ROLE OF EDUCATIONAL SUPERVISION IN IMPROVING TEACHER PROFESSIONALISM AT KARAWANG JUNIOR HIGH SCHOOL - Wahidin, Wahidin (Program Studi Manajemen Pendidikan Islam, 2024)
This research aims to evaluate educational supervision in improving teacher professionalism. Learning is a deliberate and organized effort that aims to achieve certain goals. The aim of education is to improve the quality of human potential. Increasing human resources includes improving education through the learning process in schools. To improve the quality of educational materials, it is essential to nurture and develop teachers, who play an important role in the human resources sector. The supervision process involves the guidance and assistance of educators and other staff members in carrying out their duties effectively, which is planned and implemented by the supervisor. Providing supervision is a useful way to overcome challenges faced during the learning process. Supervision in education is when supervisors help teachers combine professional skills and knowledge through speaking, demonstrating, and guiding to achieve educational goals. The research method chosen involves a qualitative descriptive approach. The data collected consists of observations, interviews and documentation. Research was conducted at SMAN 6 Karawang to determine the impact of educational supervision on increasing teacher professionalism at the school